Business process driven SOA using BPMN and BPEL : from business process modeling to orchestration and service oriented architecture - Juric, Matjaz B.; Pant, Kapil (Packt Pub., 2008)
Annotation The book provides a well-balanced mixture of theoretical discussion and real-world examples. It explains the concepts and approaches, and describes methodology and notation. It demonstrates these concepts on real-world examples and provides a step-by-step example tutorial that guides readers from business process modeling in BPMN through transformation into BPEL to execution on the SOA process server. It also discusses some key concepts using practical examples and business scenarios around Business Rules Management and Business Activity Monitoring with BPM and SOA. This book is for CIOs, executives, SOA project managers, business process analysts, BPM and SOA architects, who are responsible for improving the efficiency of business processes through IT, or for designing SOA. It provides a high-level coverage of business process modeling, but it also gives practical development examples on how to move from model to execution. We expect the readers to be familiar with the basics of SOA.
Includes index.
Title from title screen.
Keywords: Business enterprises -- Data processing.; Business -- Data processing -- Management.; Computer network architectures.; BPEL (Computer program language); Business logistics -- Data processing.; elektronické knihy; electronic books